2021
DOI: 10.1088/1755-1315/763/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in seagrass carbon stock: implications of decreasing area and percentage cover of seagrass beds in Barranglompo Island, Spermonde archipelago, South Sulawesi, Indonesia

Abstract: Seagrass ecosystems in shallow waters, including in highly dense small islands, are vulnerable to anthropogenic activities and may lead to a decreasing in seagrass area and percentage cover. As a result, it will negatively affect climate change mitigation, i.e. a decrease in seagrass carbon stock. This research was conducted to evaluate seagrass carbon stock changes in Barranglompo Island, Spermonde archipelago, in 2001 and 2017. Carbon stock estimation was carried out by collecting seagrass biomass based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, the general equation was developed by converting all the seagrass species into single equation, which might lead to error when it is applied to percent cover data. Each species has a different number of leaves, leaf size, and leaf structure which might also affect the AGC value [2].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the general equation was developed by converting all the seagrass species into single equation, which might lead to error when it is applied to percent cover data. Each species has a different number of leaves, leaf size, and leaf structure which might also affect the AGC value [2].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Global warming causes instability in the wave and tides and increasing carbon dioxide also changing seawater acidification [1]. Human disturbances such as sand dredging, reclamation, and aquaculture could also reduce the potential of carbon sinks to absorb and store carbon [2]. The degrading coastal ecosystems has become an urgent matter.…”
Section: Introductionmentioning
confidence: 99%
“…These are the types: Enhalus acoroides (Ea), Cymodocea rotundata (Cr), Thalassia hemprichii (Th), Halodule uninervis (Hu), Cymodocea serrulata (Cs), Halophila minor (Hm), Halodule pinifolia (Hp), Halophila pinifolia (Hp), Halophila ovalis (Ho), Halophila sulawesii (Hs), Syringodium isoetifolium (Si), Halophila major (Hm), and Thalassodendron ciliatum (Tc) [10]. There are various species of seagrass at one location: 4 species (Jepara [11], Berau [10]); 5 species (Jepara [13], Tunda [14], and Wakatobi [11]); 6 species (Karimunjawa [15], Makassar [16], Barranglompo [17]; 7 species (Karimunjawa [18], Lombok Barat [11], Bitung [19]); and 8 species (Lampung [11], Bintan [11]). As reported in previous studies, the maximum and lowest organic carbon stock (OCS) were found: on Karimunjawa Island, Th type (19.4±1.8 gCorg m −2 ) and Si (0.9±0.5 gCorg m −2 ) [18], and on Pramuka Island, Th type (18.22-443.73 gCorg m −2 ) and Si (5.99-25.61 gCorg m −2 ) [20].…”
Section: Introductionmentioning
confidence: 99%